A comparative study of phenotypic and genotypic first- and second-line drug resistance testing of Mycobacterium tuberculosis. (September 2017) - Sakhaee, Fatemeh; Ghazanfari, Morteza; Ebrahimzadeh, Nayereh; Vaziri, Farzam; Jamnani, Fatemeh Rahimi; Davari, Mehdi; Gharibzadeh, Safoora; Mandjin, Fatemeh Hemati; Fateh, Abolfazl; Siadat, Seyed Davar
Abstract: This study aimed to evaluate the frequency of resistance to first- and second-line drugs using phenotypic and genotypic methods and its correlation with resistance-linked mutations in Mycobacterium tuberculosis (M. tb) isolated in Iran. Three different methods, including the indirect proportion method(PM), direct and indirect nitrate reductase assay(NRA), and direct sequencing were used to assess drug resistance. In this study, sensitivity, specificity, agreement, costs, and turnaround time of these methods were compared in 395 smear positive isolates. Compared to the PM, the NRA and the direct sequencing methods demonstrated higher specificity, sensitivity, and agreement for detection of all anti-tuberculosis drugs. The NRA had a short turnaround time and was more cost-effective than the other methods. Mutations in codon 531 in rpoB, 315 in katG, 18 in rpsL, and 306 in embB were associated with high-level resistance to the first-line drugs, and mutations in codon 94 in gyrA, and A1401G in rrs were correlated with resistance to the second-line drugs. We found that the NRA is a highly sensitive, specific, inexpensive, and rapid test with strong potential to be a useful and interesting alternative tool, particularly in low-income countries. In addition, these molecular data will be helpful for developing new molecular methods for detecting first- and second-line drug-resistant M. tb.